Does Larger Fetal Ascending Aorta Than the Pulmonary Artery Indicate Major Cardiac Anomaly? - Baran, Safak Yilmaz; Arslan, Alev; Dogan Durdag, Gulsen; Kalayci, Hakan; Yuksel Simsek, Seda; Alemdaroglu, Songul (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: This study investigated the cases in which the fetal ascending aorta is larger than the main pulmonary artery on the three-vessel view and aimed to determine the relationship between the larger ascending aorta and major cardiac anomalies. STUDY DESIGN: Pregnancies between 18-24 gestational weeks who underwent detailed second-trimester screening during 2015-2019 were evaluated. Cases whose fetal ascending aorta diameter was larger than fetal main pulmonary artery diameter on the three-vessel view despite normal four-chamber view were analyzed. Prenatal and postnatal echocardiography studies were performed for each case. RESULTS: Fetal ascending aorta diameter larger than fetal main pulmonary artery diameter on the three-vessel view despite normal four-chamber view was detected in 21 fetuses in a total of 3810 pregnancies (0.55%), and 10 (47.6%) of them had major congenital heart disease. The diagnosis of Tetralogy of Fallot, double outlet right ventricle, ventricular septal defect, pulmonary valve stenosis, and moderate to severe tricuspid regurgitation were confirmed with prenatal/postnatal echocardiography studies. The highest ratio of ascending aorta/main pulmonary artery was 1.4 in a fetus with a double outlet right ventricle and pulmonary valve stenosis. CONCLUSION: The fetal ratio of ascending aorta/main pulmonary artery larger than 1 on the three-vessel view may be a sign of certain cardiac anomalies. Nevertheless, this rate is not an indicator of a serious cardiac defect in all cases. Fetal advanced echocardiography and early postnatal cardiac evaluation should be done to confirm the diagnosis.